Diversity statements for leveraging organizational legitimacy - Singh, Val; Point, Sébastien (Management international / Gestiòn Internacional / International Management, 2009)
AbstractEuropean companies are increasingly putting “diversity statements” on corporate websites. Websites are important because they are used by members of the public, especially the younger generation, to seek information about companies. Legitimacy theory is often cited as one explanation for having good diversity policies, but we found no research in the diversity, HRM or social accounting literature with empirical evidence of different types of legitimacy associated with diversity. We examined on-line diversity statements from 174 top European companies for evidence of legitimacy-enhancing messages, and coded them by type of legitimacy. We show that diversity statements are presented in ways associated with two different types of legitimacy (pragmatic exchange and moral). International differences are also highlighted. These findings will help practitioners to design diversity statements based on a better understanding that legitimacy is a multi-faceted construct, and help them avoid the dangers of empty discourse, i.e. inconsistency between words and reality.